The AARP caregiver answer book - Jacobs, Barry J.; Mayer, Julia L. (The Guilford Press, 2025)
"We've met more and more people in recent years who are new to caregiving and have questions. More older adults and individuals with disabilities need care and more of it. More relatives and even friends will be asked to step up and provide it. The purpose of this book is to answer the most common caregiving questions we have heard over the years so that you can focus on the tasks at hand with competence and confidence. Chapter 1 provides an overview of what caregiving entails and defines terms you'll encounter throughout this important work. Chapter 2 helps you assess your situation, which involves what the recipient of your care needs and what you are willing, able, and available to provide. Chapter 3 explains how you can successfully take on one of the biggest challenges caregivers face and one of the most important-taking care of yourself. Chapter 4 explores tools and skills for effective communication but also for communicating with respect, empathy, and kindness. Parents are the most common receivers of care and are the subject of Chapter 5. Caring for a partner, usually the most stressful caregiving situation, is discussed in Chapter 6. Chapter 7 answers common questions about caring for someone with cognitive impairment or dementia. Chapter 8 provides answers about mobility issues, medication management, bathroom assistance, and more. Chapter 9 answers questions about how to know when your care receiver requires a higher level of care. Chapter 10 leads you through the complex maze of finances and money management related to caregiving. Chapter 11 offers ideas for collaborating effectively with siblings and other relatives. Chapter 12 provides suggestions for approaching medical and other professionals, managing your relationship with them, and getting the most out of these important connections. Finally, Chapter 13 addresses your concerns about what happens as your care receiver declines and approaches the end of life"-- Provided by publisher.